Allegations Of A Cartel In Online Loan Service In The Enforcement of Business Competition Law - Zulkifli; Wetria Fauzi (Ekasakti Journal of Law and Justice, 2025)
The regulation of online loan interest rate determination in Indonesia is regulated in the Guidelines for the responsible provision of information technology-based money lending services issued by the Indonesian Joint Funding Fintech Association (AFPI) and the association has the authority based on statutory regulations to determine loan interest rates and other fees for business actors engaged in the online loan service sector. A cartel occurs when several business actors agree to regulate: interest rates, minimum/maximum loan limits, division of marketing areas or control of prospective debtor data. The Business Competition Supervisory Commission stated that AFPI and its members were involved in an alleged online loan interest rate cartel and an investigation has been conducted into the allegation. The investigation has found that there is an agreement to determine online loan interest rates carried out by AFPI and its members and the KPPU has also found 44 reported parties in this case and found evidence to strengthen the allegation including statements from the reported parties, witnesses or experts who have relevance to this case and other evidence. Synergy between institutions and the application of digital monitoring technology are the main keys to preventing the formation of cartels in the online loan sector.